Kesenian Dongkrek Sebagai Upaya Untuk Menyikapi Covid 19 Di Kota Madiun - Ningrum, Fiki Surya; Widodo, Wahono; Istig’faroh, Nurul (CV. Kurnia Grup, 2024)
This study aims to determine the meaning of the use of dongkrek art as local wisdom in an effort to respond to Covid-19 in Madiun City and to explore the material content in dongkrek art, and integrate dongkrek art with learning in elementary schools. This type of research is qualitative with an ethnographic method that uses data collection techniques in the form of interviews and observations. The results show that the community carries out mitigation with various activities through supernatural powers and horizontally by establishing good relationships with fellow humans and nature. Dongkrek is a regional art native to Mejayan Village, Mejayan District, Caruban, Madiun City, East Java, Indonesia. This art is in the form of dance and musical accompaniment that tells the story of Raden Ngabei Lo Prawirodipuro's efforts in overcoming the plague. At that time, the Mejayan community was hit by an epidemic. It is said that if in the morning they were sick, they would suddenly die in the afternoon, likewise when they were sick in the afternoon, they would die in the morning. As an effort to overcome the plagueblug, Raden Ngabei Lo Prawirodipuro, who at that time served as Demang, created the dongkrek dance and music. This art is believed to have magical powers to ward off disease and bring safety. Raden Ngabei Lo Prawirodipuro's efforts to ward off the plagueblug were through the movements and accompaniment of dongkrek music which contained symbols that symbolized the struggle against disease and evil forces. This dance also contains prayers and hopes that the community will be given health and prosperity. Dongkrek art is not just dance and music, but also a reflection of the history and culture of the Madiun community. Through Dongkrek, we can learn a lot about noble values, cultural resilience, and the importance of preserving ancestral heritage. The noble values contained in dongkrek must be maintained and preserved. This art is one of the cultural identities of the City of Madiun.